The value of connections in turbulent times: Evidence from the United States - Acemoglu, Daron; Johnson, Simon; Kermani, Amir; Kwak, James; Mitton, Todd (Journal of Financial Economics, 2016)
The announcement of Timothy Geithner as nominee for Treasury Secretary in November 2008 produced a cumulative abnormal return for financial firms with which he had a prior connection. This return was about 6% after the first full day of trading and about 12% after ten trading days. There were subsequently abnormal negative returns for connected firms when news broke that Geithner’s confirmation might be derailed by tax issues. Personal connections to top executive branch officials can matter greatly even in a country with strong overall institutions, at least during a time of acute financial crisis and heightened policy discretion.